Issue Notes - , Editor (Historical Papers, 2022)
The papers presented by Victoria Netton (“Planters and Parsons: A Symbiotic Relationship in the Church of England in Newfoundland between 1699-1750”), Russell Prime (“‘High Time for the Courtship to Begin’: Overtures for Union between Baptists and Disciples of Christ in the Maritime Provinces, 1907-1910”), Gary Miedema (“Pluralism, Tolerance and Division: Negotiating the Representation of Religion at Expo 67”), Douglas H.Shantz (“In Weakness Strength: The Common Pietist Archetype for Men’s and Women’s Spiritual Autobiographies”), Jack Little (“The Circuit Rider Revisited: the Wesleyan Methodist Missionaries of the Eastern Townships”), Gordon Heath (“Canadian English Protestants and the South African War, 1899-1902”), Louise Johnston (“The Iroquois Thanksgiving Address”), and Elizabeth Elbourne (“Anna Gurney: Women, Religion and Female Political Activism in Victorian Britain”), were not made available for publication.